Google dataset search and DOI for data in the ESA space science archives. Issue 8 (15th April 2021) - Masson, Arnaud; De Marchi, Guido; Merin, Bruno; Sarmiento, Maria H.; Wenzel, David L.; Martinez, Beatriz
Abstract: Reproducibility is at the core of science. For this reason, a common practice for authors is to provide links to the data used in their manuscripts upon submission to peer-reviewed journals. In space science, reference to archives' websites of major data providers like space agencies are still accepted by most journals. However, even these websites are not persistent links and will eventually not be accepted once journals require full compliance with the FAIR (Findable, Accessible, Interoperable, and Reusable) data principles. On the contrary, Digital Object Identifiers (DOIs) associated to data could provide persistent links. But so far, the publishing industry is systematically minting DOIs related to their articles or books without requiring DOIs for the data used in their publications. Furthermore, DOIs related to data would not only link refereed publications to the data location. It could also enable a more precise attribution to the data producers and publishers while providing the capability to eventually trace their use. These latter points require that journals eventually request or even enforce the use of these DOIs. For data producers, proper attribution and usage are important in the context of securing research grants or extension of projects. Additionally, structured metadata included in the DOI landing pages offer the possibility for datasets to be discoverable by the new Google Dataset Search (GDS) engine, available since January 2020. This paper describes the on-going activities at the European Space Agency (ESA) to mint DOIs for datasets served across the space science archives, and how a subset of these DOIs are already discoverable by GDS.